Audit services market: bibliometric analysis - Iryna Vyhivska; Вигівська Ірина; Gabriella Loskorikh; Лоскоріх Габріелла; Loszkorih Gabriella (Державний університет "Житомирська політехніка", 2023)
Abstract. Modern challenges in doing business and functioning of enterprises, implementation of sustainable development goals require adaptation of Ukrainian legislation to international, in particular European, standards, including the sphere of audit activities. An audit is a reliable way to confirm the reliability and confidence of information about the financial statements and financial condition of an enterprise. The article considers the regulatory framework for the concepts of «audit» and «audit activity». The market of audit services is studied and its components are identified: the provision of audit, non-audit and related services by audit entities. Along with this, the analysis of the audit services market and the problems of providing audit services and, directly, conducting an audit is carried out. In the course of the study, methods of visualization of the main areas of research of scientists, publication activity of authors based on data from the Scopus scientometric database using VOSviewer and Bibliometrix software were used. Bibliometric, structural, cluster, and graphical analyses were used. The applied research methods in the field of audit activity made it possible to identify the leading countries in terms of publication activity of the topic under study. The most cited articles are presented, which are aimed at determining the most relevant areas of research of scientists and further monitoring of problematic issues.

Резюме. Сучасні виклики щодо ведення бізнесу та функціонування підприємств, запровадження цілей сталого розвитку вимагають адаптації українського законодавства до міжнародних, зокрема європейських, норм, враховуючи сферу аудиторської діяльності. Аудит є надійним способом підтвердження достовірності та впевненості інформації щодо фінансової звітності та фінансового стану підприємства. У статті розглянуто нормативно-правову базу поняття «аудит» та «аудиторська діяльність». Досліджено ринок аудиторських послуг та ідентифіковано його складові: надання суб’єктами аудиторської діяльності аудиторських, неаудиторських та супутніх послуг. Водночас проведено аналіз ринку аудиторських послуг та проблематики надання аудиторських послуг та безпосередньо проведення аудиту. У процесі дослідженні були використані методи візуалізації основних напрямів дослідження вчених, публікаційна активність авторів за даними науковометричної бази Scopus за допомогою програмного забезпечення VOSviewer та Bibliometrix. Використано бібліометричний, структурний, кластерний та графічний аналіз. Застосовані методи дослідження у сфері аудиторської діяльності дозволили визначити країни-лідери щодо публікаційної активності досліджуваної теми. Наведено найбільш цитовані статті, які спрямовані на визначення найактуальніших напрямів дослідження вчених та подальшого моніторингу проблемних питань.
Ринок аудиторських послуг: бібліометричний аналіз
Весь випуск: https://pbo.ztu.edu.ua/issue/view/17030
Keywords: audit services market; auditing activities; audit; financial reporting; non-financial reporting